Media impacts recovery of Salmonella enterica and Enterococcus faecium NRRL B2354 from whole black peppercorns, basil leaves, and chia seeds treated with antimicrobial gasses - Garcia, Jose O; Wason, Surabhi; Subbiah, Jeyamkondan; Eifert, Joseph; Strawn, Laura K.; Ponder, Monica A. (Frontiers in Food Science and Technology, 2022)
Salmonella enterica contamination of low water activity foods (LWAFs) has resulted in recalls of spices, herbs, and seeds and outbreaks of salmonellosis. To improve the safety of these ready-to-eat products, new treatment methods, including fumigation with chlorine dioxide (ClO2) or hydrogen peroxide (H2O2) gas are being explored, and effectiveness determined. To prevent overestimation of treatment effectiveness, it is vital that recovery methods should accurately quantify all viable cells, even those injured. This study evaluated different media and supplements for the recovery of multiple strains of S. enterica and Enterococcus faecium NRRL B2354, from ClO2 or H2O2 treated black peppercorns, dried basil leaves, and chia seeds. Also, this study aimed to compare the log reduction of these two microorganisms to evaluate E. faecium NRRL B2354, as a surrogate for S. enterica. On average, recovery of S. enterica was improved by 1 log CFU from ClO2 and H2O2 treated LWAFs when a non-selective but differential media containing tryptic soy agar with yeast extract, ammonium iron citrate and sodium thiosulfate (MTSAYE) was used, when compared to plating on XLD (p < 0.05). Furthermore, addition of sodium pyruvate, ferrous sulfate, or 3’3’-thiodiproionate supplements to MTSAYE did not show increased recovery of either S. enterica or E. faecium NRRL B2354 (p > 0.05). On each treatment and LWAF combination tested, there was no significant difference between the log reduction of S. enterica and E. faecium NRRL B2354, indicating its suitability as a surrogate under the test conditions.